MENINGKATKAN LAYANAN PRIMA DI ERA DISRUPTIF : TANTANGAN BAGI PUSTAKAWAN - Nur Sanny Rahmawati (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
Introduction. Service excellence is the main thing librarians should provide, and it is no exception with current technological developments. This rapid technological development makes information becomes easy and fast to access. Therefore, librarians as knowledge organizer and information dissemination agents need to continually update their knowledge and competencies in order to provide quality services for library users. Purpose. This study aims to find out how best service should be provided by librarians to users in the midst of the current disruptive era of technology. Method. Qualitative method by studying literature was used in this study. Results and discussion. The study shows that technology-based library services such as promotion through social media, VR-AR-based service, and android-based library applications are excellent forms of services librarians can provide to users. This should be balanced by constantly increasing librarian’s competencies, for example, their proficiency in the use of information technology, knowledge management, management and leadership, and by enhancing their excellent communication skills and attitudes in giving services.